The ‘special cassava flour’: perception and processing of a smallholder agriculture product in the Juruá River valley, Acre - Lucia Hussak van Velthem; Esther Katz (Boletim do Museu Paraense Emílio Goeldi. Ciências Humanas, 2012)
Smallholders from upper Juruá river valley, state of Acre, in Brazil, produce cassava flour (farinha de mandioca) for consumption and trade. This article describes the practices that produce and identify a 'special' cassava flour from the point of view of the local producers. These processes are both technical and conceptual, and they apply to the cassava roots, the objects associated to its processing and the cassava flour produced, differing from the assessment of traders and governmental institutions. This prescriptive set will be faced with the perception of traders and also with the public service, which operates in this production improvement considering it undervalued and with high variability.